The process of human resources management in educational institutions - Kurowicka, Ewelina (Journal of Education, Health and Sport, 2019)
Human resources determine the effectiveness of the enterprise and the level of services provided to clients. The most important elements of the human resource include: motivation, knowledge, skills, health, skills, attitudes and values. This article deals with topics related to human resource management in educational institutions. The text shows the essence, meaning and elements of human resource management at school. Theoretical considerations were supplemented with an indication of the role of the director in personnel management.